Metal replacement in "zinc finger" and its effect on DNA binding. - Predki, P F; Sarkar, B (1994)
Metal replacement studies were used to investigate the metal requirement of a bacterially expressed polypeptide encoding the zinc finger DNA binding domain of the estrogen receptor. Apopolypeptide was generated by dialysis of native polypeptide against low-pH buffer under reducing conditions. Specific DNA binding can be restored by refolding the apopolypeptide in the presence of ionic zinc, cadmium, or cobalt. However, refolding in the presence of copper or nickel fails to regenerate DNA binding activity. While cobalt-reconstituted polypeptide has a reduced affinity for its AGGTCA-binding site compared to zinc- or cadmium-polypeptide, it has the surprising property of increased cooperative DNA binding. Our work indicates that metal substitution results in a range of effects upon DNA binding in vitro. The potential biological significance of metal substitution in vivo is discussed.